Formation of an Assessment of Audit Services in Audit Organizations - M. A., Abduganiyev (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article examines the issues of setting prices for services provided by audit organizations. In particular, internal and external factors affecting the assessment of services provided by an audit organization, as well as methods for assessing services, were studied.